The Influence Of Foreign Direct Investment, Wage Level, Tourism Industry and Regional Native Income on Products Domestic Regional Bruto - Puja Dego Asmara (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. High GRDP (Gross Regional Domestic Product) growth can attract investor interest, stimulate investment, and encourage infrastructure development, leading to increased connectivity and economic efficiency. Furthermore, strong GRDP growth can create additional labor demand, potentially reducing poverty and raising income levels. Purpose. This research aims to examine the factors influencing GRDP in Indonesia, specifically focusing on foreign direct investment (FDI), wage levels, the tourism industry, and regional original income (PAD), using data from 2020 to 2022. Method. The study employs a quantitative approach, utilizing panel data obtained from the Indonesian Central Statistics Agency (BPS) from 2020 to 2022. Multiple Linear Regression analysis is applied to assess the relationship between GRDP and the selected independent variables: FDI, wage levels, tourism, and PAD. Results. The results indicate that FDI has a significant positive effect on GRDP, with a t-value of 6.264, which is greater than the critical value of 1.66196. Conversely, wage levels and the tourism industry do not show a significant impact on GRDP, with respective probability values of 0.39 and 0.254, both below the threshold. Meanwhile, PAD has a significant positive effect on GRDP, with a t-value of 4.904, also exceeding the critical value of 1.66196. Conclusion. This study concludes that FDI and regional original income (PAD) are significant contributors to GRDP growth in Indonesia, while wage levels and the tourism sector do not have a notable impact on regional economic performance during the observed period.